(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Metabolic syndrome (MetS) is the co-occurrence of cardiovascular risk factors that include obesity, hypertension, dyslipidemia and insulin resistance. Hyperuricemia is frequently observed in people with MetS and may contribute to cardiovascular and renal risk. Because hyperuricemia commonly co-occurs with MetS components, establishing its prevalence may improve cardiometabolic risk stratification and prevention of renal and cardiovascular complications. Objectives: To determine the prevalence of hyperuricemia in individuals with metabolic syndrome and its association with patient age, sex, or other demographic parameter of the patients or also to their other metabolic risk factors and overall disease burden in our study population cohort. Study Design: A cross-sectional study. Place and Duration of study: From December 2024 to May 2025 in General Medicine Department, Bolan Medical Complex Hospital Quetta. Methods: A cross-sectional study was conducted in the Department of Medicine, Bolan Medical Complex Hospital, Quetta from December 2024 to May 2025, including 120 patients with metabolic syndrome (NCEP-ATP III criteria). Serum uric acid was measured enzymatically; hyperuricemia was defined as >7.0 mg/dL in men and >6.0 mg/dL in women. Demographic, clinical, and biochemical data were collected. Exclusions included CKD, gout, hematological disorders, or uric acid–altering medications. Data were analyzed using SPSS 24, with t-tests and chi-square tests (p<0.05). Results: A total of 120 patients with metabolic syndrome were included (mean age 52.6 ± 9.4 years). Hyperuricemia was present in 58 patients (48.3%). The prevalence of hyperuricemia was higher in males (52%) than in females (44%), but this difference was not statistically significant (p = 0.09). Hyperuricemia was significantly associated with higher triglycerides (p = 0.03), hypertension (p = 0.04) and increased waist circumference (p = 0.02). No significant difference in fasting glucose was observed between groups (p= 0.12). Patients with ≥3 components of metabolic syndrome had a higher prevalence of hyperuricemia than those with fewer components (p = 0.01) Conclusion: Hyperuricemia was present in almost half of the patients with metabolic syndrome and was significantly associated with hypertension, abdominal obesity and dyslipidemia. These findings support the inclusion of serum uric acid measurement in the comprehensive risk assessment of patients with metabolic syndrome. Prospective studies are needed to determine whether early detection and treatment of hyperuricemia reduce long-term cardiovascular and renal outcomes, particularly in high-risk individuals with multiple metabolic risk factors.